Best practices for Impact Benefit Agreements. (March 2021) - Cascadden, Maggie; Gunton, Thomas; Rutherford, Murray
Abstract: Impact benefit agreements (IBAs) are an increasingly common tool in resource development. However, the effectiveness of IBAs in achieving community and development objectives can vary widely depending on the negotiating process, the components of the IBA, and implementation and management of the IBA. This paper provides a comprehensive best practices framework for developing and managing IBAs from the perspective of impacted communities, based on a synthesis of recommendations from academic, industry, governmental, and non-governmental organization literature. The best practices are presented in a three-tier model comprised of 10 general best practice criteria, 44 sub-criteria and 89 indicators. The criteria are presented in the form of a checklist that can be used to guide the negotiation, implementation and management of IBAs and to conduct ex post IBA evaluations. While the best practices have been developed from the perspective of impacted communities to achieve better IBA outcomes, these best practices will also be helpful to academics and others who want to evaluate IBAs, and to resource developers who are interested in negotiating effective IBAs with their community partners. Highlights: Impact benefit agreements often fail to meet goals of communities and developers. We developed a comprehensive best practices framework for Impact Benefit Agreements. 10 general best practice criteria, 44 sub-criteria and 89 indicators. Checklist for negotiation, implementation and management of Impact Benefit Agreements. Useful for affected communities, academics, resource developers and evaluators.